PENGARUH EDUKASI TERHADAP PENGETAHUAN SISWA TENTANG HIV/AIDS DI TANGERANG TAHUN 2020 - Peni Surya Listyana; Meynur Rohmah (Nusantara Hasana Berdikari, 2021)
The prevalence of ODHA in the world in 2017 is 36.9 billion people, which has just freed 1.8 billion people. Of these there are 21.7 billion people living with HIV who have received antiretroviral treatment and including 940,000 people living with HIV (WHO, 2018). HIV / AIDS sufferers in Indonesia also experience an increase every year. A report from the Indonesian Ministry of Health in 2018 revealed that the number of reported cases of HIV cases was 301,959 people (47% of the estimated number of people living with HIV / AIDS or ODHA) in 2018 of 640,443 people, the condition in Indonesia was 75% infected with HIV from the age group adolescents (Pusdatin Kemenkes RI, 2018). Methods : Researchers used data bases such as google scholar, pubmed, researchgate to search for articles by authors searching Indonesian and English with the keywords